Customer relationship management: Ethics in the use and handling of data in Intelligent Information System - Bernal Barbosa, Laura Beatriz (2021)
Today, due to the opening of markets, companies face a higher level of competition, which is why it is extremely important to have strategies to attract, retain and better understand customers in order to provide better products and services that allow them be more competitive. Likewise, due to the large volume of clients, companies require tools and strategies for the analysis and management of data that facilitate them to make better decisions. Faced with this need, the purpose of this paper is to conceptualize the Customer Relationship Management system, emphasizing the use of smart information systems, as well as the ethical implications of the information collected from customers. For this, a scientific literature review focused on the subject was carried out. It was determined that the system allows organizing and analyzing customer information by identifying their needs and preferences in an automated way, favoring decision-making, increasing loyalty relationships with the customer and generating sustainable competitive advantages. Similarly, the importance of establishing ethical practices in the management of information collected from clients is specified, which can be achieved in compliance with the laws of each country or by establishing codes of ethics in each organization.